A rationally designed 3D interconnected porous tin dioxide cube with reserved space for volume expansion as an advanced anode of lithium-ion batteries. Issue 71 (5th August 2020) - Kong, Shuyi; Xu, Jijian; Lin, Gaoxin; Zhang, Shaoning; Dong, Wujie; Wang, Jiacheng; Huang, Fuqiang
Abstract : A porous SnO2 cube with rational designed reserved space (∼375%) is synthesized via an artful topochemistry route (CaSn(OH)6 –CaSnO3 –SnO2 ). Abstract : To work against the volume expansion (∼300%) of SnO2 during lithiation, here a sub-micro sized, interconnected, and porous SnO2 cube with rationally designed reserved space (∼375%) is synthesized via an artful topochemistry route (CaSn(OH)6 –CaSnO3 –SnO2 ). Owing to its microstructure, this novel material harvests enhanced lithium-storage performance.